Recognition of Pathogenic Free-Living Amoebae in the Surface Water in Shiraz, Iran - Behnam Mohammadi- Ghalehbin; Gholam Reza Hatam; Iraj Mohammad-Pour; Nafise Ghobakhloo; Faeze Foroughi- Parvar (Shiraz University of Medical Sciences, 2014)
Background: There are many genera of free-living amoeba in the environment, but members of only four genera (Naegleria, Acanthamoeba, Balamuthia and Sappinia) have an association with human infection. Water, soil and air are main sources of infective types of these pathogenic organisms for human.Methods: Totally, 30 samples were collected from the surface water sources of Shiraz city, the capital of Fars province, during July and August 2009. The samples were filtered and their sediments were cultured on non-nutrient agar medium and seeded with non-pathogen Escherichia coli. Then, they were incubated at three different temperatures, 22˚C, 37˚C, and 44˚C. The media were checked with invert microscopy and amoebae were recognized by phase-contrast microscopy and observed by light microscopy after Trichrome staining. Polymerase chain reaction (PCR) was performed for molecular detection.Results: Of the 30 samples, 29 were recognized morphologically as Acanthamoeba, the characteristics of 20 of which were confirmed by PCR. The growth rate of amoeba in 22˚C was more than 37˚C. Eight of the samples grew at 44˚C, but flagellate forming test and PCR were negative for Naegleria fowleri. Two of them were identified morphologically as Balamuthia and Sappinia.Conclusion: Since Fars province is located in the subtropical region where there are a lot of parks and green areas with surface water, the potential risk of diseases caused by free-living amoebae should be considered. Further investigations about various aspects of these important opportunistic protozoa are recommended especially for establishment of appropriate prevention tools.